PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Furniawan Furniawan (Universitas La Tansa Mashiro, 2022)
Every company certainly has its own goals, and the key to success in achieving company goals is management achievement. However, in an effort to realize the company's goals, the company must maximize its funding needs in order to optimize its performance. The research method uses a type of quantitative research. This quantitative research is intended to provide an overview and explain the financial performance depicted through financial reports. The population in this research is consumer goods companies, food and beverage sub-sector which are listed on the Indonesia Stock Exchange, totaling 18 companies. a sample of 10 companies, with observations for 6 years, so that the sample obtained by the number of observations of 60 data. Based on the results of the previous research and discussion, the authors can conclude that the partial test results for the leverage variable on PBV firm value mean that it has a significant effect on firm value. Partial test results for the variable firm size on firm value PBV means that firm size has a significant effect on firm value. Simultaneous test results for the leverage variable and firm size variable on firm value means that leverage and firm size have a significant effect simultaneously on firm value.